Phytochemical Screening and Antibacterial Activity of Leaf Extracts from Psiadia Punctulata - Samer, Bushra S.; Al-Mausmi, Hadi; Gailan, Amar; Ziad, Sultan; Saleh, Mohammed; Shalan, Abdullah; Hamdan, Mohammed; Gharab, Abdullah; Al-Ra'ai , Ashraf; Al-Ra’ai, Najam Al-Din; Al-Ezzi, Mona (Thamar University Journal of Natural & Applied Sciences, 2024)
Background: Psiadia punctulata (P. punctulata) is a delicate medicinal herb commonly used in traditional herbal therapy. Objective: To identify the phytochemical constituents and assess the antibacterial efficacy of methanolic extracts of Psiadia punctulata. Materials and Methods: The plant material was collected, shade-dried, and then powdered. The powder was soaked and macerated in methanol, followed by extraction using the Soxhlet method. Phytochemical tests were conducted qualitatively. Antibacterial activity was evaluated using different types of bacteria and compared with various antibiotics. Results: The P. punctulata plant showed the presence of alkaloids, tannins, phenols, flavonoids, cardiac glycosides, steroids, and terpenoids. The extract exhibited significant inhibition zones against Staphylococcus epidermidis (28 mm) and Escherichia coli (30 mm). Conclusion: This study revealed that Psiadia punctulata contains a wide range of secondary metabolites with antibacterial properties.